2013
DOI: 10.4236/ojemd.2013.32016
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity and Kidney Function Decline among Non-Diabetic Adults with eGFR > 60 ml/min/1.73m<sup>2</sup>: Results from the Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: BackgroundObesity is associated with higher end-stage renal disease incidence, but associations with earlier forms of kidney disease remain incompletely characterized.MethodsWe studied the association of body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) with rapid kidney function decline and incident chronic kidney disease in 4573 non-diabetic adults with eGFR ≥ 60 ml/min/1.73m2 at baseline from longitudinal Multi-Ethnic Study of Atherosclerosis cohort. Kidney function was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…We were unable to fully adjust for risk factors such as glycated haemoglobin, diabetes duration, or drug treatments, which could contribute to the association between obesity and GFR decline. Other filtration markers such as cystatin C were not available to estimate GFR 25 ; however, our results were consistent in analyses using ESKD alone as the outcome. We lacked uniform data on trends in blood pressure control, and thus could not examine whether heterogeneity was explained by differences in treatment intensity.…”
Section: Discussionsupporting
confidence: 78%
“…We were unable to fully adjust for risk factors such as glycated haemoglobin, diabetes duration, or drug treatments, which could contribute to the association between obesity and GFR decline. Other filtration markers such as cystatin C were not available to estimate GFR 25 ; however, our results were consistent in analyses using ESKD alone as the outcome. We lacked uniform data on trends in blood pressure control, and thus could not examine whether heterogeneity was explained by differences in treatment intensity.…”
Section: Discussionsupporting
confidence: 78%
“…Race and ethnicity were adjusted for, but not reported separately in this analysis. 29 Conversely, in the CARDIA STudy Grubbs et al reported obesity is associated with incident CKD. 30 Waist circumference and BMI were not associated with rapid decline in this evaluation of the JHS population; however, most subjects had an elevated BMI at baseline.…”
Section: Discussionmentioning
confidence: 97%
“…Obesity has been shown to be a risk factor for cardiovascular disease (CVD) and chronic kidney disease (CKD). [1][2][3] The prevalence of CKD is increasing worldwide, and the economic burden of its treatment is increasing. Therefore, it is essential to prevent the progression of CKD by detecting renal dysfunction early.…”
Section: Introductionmentioning
confidence: 99%
“…This classification reflects body fat distribution more accurately than describing obesity based only on BMI or the presence of metabolic syndrome. [14][15][16][17] Although several studies have suggested that obesity is associated with early renal dysfunction, 3,6) very few studies have focused on the association between early renal dysfunction and obesity phenotypes in adults without HTN, dyslipidemia, and diabetes.…”
Section: Introductionmentioning
confidence: 99%